PD-1 Immune Checkpoint Blockade and PSGL-1 Inhibition Synergize to Reinvigorate Exhausted T Cells - Viramontes, Karla M.; Neubert, Emily N.; DeRogatis, Julia M.; Tinoco, Roberto (Frontiers in Immunology, 2022)
Chronic viral infections where the antigen persists long-term, induces an exhaustion phenotype in responding T cells. It is now evident that immune checkpoints on T cells including PD-1, CTLA-4, and PSGL-1 (Selplg) are linked with the differentiation of exhausted cells. Chronic T cell receptor signaling induces transcriptional signatures that result in the development of various exhausted T cell subsets, including the stem-like T cell precursor exhausted (Tpex) cells, which can be reinvigorated by immune checkpoint inhibitors (ICIs). While PSGL-1 has been shown to inhibit T cell responses in various disease models, the cell-intrinsic function of PSGL-1 in the differentiation, maintenance, and reinvigoration of exhausted T cells is unknown. We found Selplg-/- T cells had increased expansion in melanoma tumors and in early stages of chronic viral infection. Despite their increase, both WT and Selplg-/- T cells eventually became phenotypically and functionally exhausted. Even though virus-specific Selplg-/- CD4+ and CD8+ T cells were increased at the peak of T cell expansion, they decreased to lower levels than WT T cells at later stages of chronic infection. We found that Selplg-/- CD8+ Tpex (SLAMF6hiTIM3lo, PD-1+TIM3+, TOX+, TCF-1+) cell frequencies and numbers were decreased compared to WT T cells. Importantly, even though virus-specific Selplg-/- CD4+ and CD8+ T cells were lower, they were reinvigorated more effectively than WT T cells after anti-PD-L1 treatment. We found increased SELPLG expression in Hepatitis C-specific CD8+ T cells in patients with chronic infection, whereas these levels were decreased in patients that resolved the infection. Together, our findings showed multiple PSGL-1 regulatory functions in exhausted T cells. We found that PSGL-1 is a cell-intrinsic inhibitor that limits T cells in tumors and in persistently infected hosts. Additionally, while PSGL-1 is linked with T cell exhaustion, its expression was required for their long-term maintenance and optimal differentiation into Tpex cells. Finally, PSGL-1 restrained the reinvigoration potential of exhausted CD4+ and CD8+ T cells during ICI therapy. Our findings highlight that targeting PSGL-1 may have therapeutic potential alone or in combination with other ICIs to reinvigorate exhausted T cells in patients with chronic infections or cancer.